The Serum Concentration of the Calcium Binding Protein S100B is Positively Associated with Cognitive Performance in Older Adults - Lam, Virginie; Albrecht, Matthew; Takechi, Ryusuke; Giles, Corey; James, Anthony; Foster, Jonathan; Mamo, John C. (Frontiers in Aging Neuroscience, 2013)
S100B is a calcium-binding peptide produced predominantly by astroglial cells in the central nervous system. S100B paradoxically has neurotrophic and apoptotic effects, dependent on extracellular concentration. This study investigated the relationship between serum S100B levels and neuropsychological performance across a range of cognitive domains in healthy older aged adults. A cohort of 219 participants between the ages of 43 and 84 years (141 female) were recruited. Subjects provided a fasting blood sample for S100B measurement (Mean = 0.24 ng/mL, SD = 0.14) and completed a battery of neuropsychological tests. S100B concentrations (both with and without the covariates of age and sex) were positively associated with the following measures of cognitive performance: digit symbol coding, Stroop test and measures of verbal ability. The results from this study show that serum S100B is positively associated with better cognitive performance in healthy older adults.